2021
DOI: 10.3390/ph14111176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Chlorogenic Acid Analogues Comprising Pyridine and Pyrimidine on α-MSH-Stimulated Melanogenesis and Stability of Acyl Analogues in Methanol

Abstract: In continuation of studies for α-MSH stimulated melanogenesis inhibitors, we have evaluated the design, synthesis, and activity of a new series of chlorogenic acid (CGA) analogues comprising pyridine, pyrimidine, and diacyl derivatives. Among nineteen synthesized compounds, most of them (fifteen) exhibited better inhibitions of melanin formation in B16 melanoma cells. The results illustrated that a pyridine analogue 6f and a diacyl derivative 13a of CGA showed superior inhibition profiles (IC50: 2.5 ± 0.7 μM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In melanoma B16 cells, CGA likely acts on melanin as a substrate, but its metabolites may inhibit melanogenesis by suppressing tyrosinase activity [311]. CGA and caffeic acid derivatives inhibit melanocyte-stimulating hormone (α-MSH)-induced melanogenesis [312][313][314]. CGA binds to tyrosinase.…”
Section: Anti-melanogenesis Effects (Figure 1h)mentioning
confidence: 99%
See 1 more Smart Citation
“…In melanoma B16 cells, CGA likely acts on melanin as a substrate, but its metabolites may inhibit melanogenesis by suppressing tyrosinase activity [311]. CGA and caffeic acid derivatives inhibit melanocyte-stimulating hormone (α-MSH)-induced melanogenesis [312][313][314]. CGA binds to tyrosinase.…”
Section: Anti-melanogenesis Effects (Figure 1h)mentioning
confidence: 99%
“…Molecular docking simulation and in vitro kinetic assay [312][313][314][315] Inhibition of α-MSH [312][313][314]; inhibition of tyrosinase [315] CGA [282]; leukemia cell lines U937, and HL60 [284,285]; lung cancer cell line A549 [287]; melanoma C32 and B16F10 [288,289]; glioma cells U87 [290]; osteosarcoma cell lines U2OS, MG-63, and Saos-2 [294,295]; pancreatic carcinoma PANC-1 [297,298]; prostate cancer cell DU145 [300]; and RCC A498 cells [301]; tumor-bearing SCID mouse models [282,287] Increase in p53, Bax, and the ratio of Bax/Bcl-2 [276,277]; blockages of (1) p-STAT-5 and p-CrkL [283,287], (2) the NF-kb pathway [276], (3) the STAT3/Snail pathway [294,295], (4) the PI3K/Akt/mTOR pathway [301], and EMT [276] CGA Cancer management in patients (Section 7.12)…”
Section: Pathogen Infectionsmentioning
confidence: 99%
“…Chlorogenic acid analog consisting of pyridine, pyrimidine motifs, and cyclohexyl ester analog showed strong inhibitory activity against melanin production in B16 melanoma cells on α-MSH stimulation. The study showed that the pyridine and diacyl chlorogenic acid cyclohexyl ester analog had a significantly superior inhibitory potential than kojic acid [8]. Other chlorogenic acid derivatives containing thiazole possess anti-hyperpigmentation activity evaluated through α-MSH-induced melanogenesis in B16 mouse melanoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…The N-substituted 2-aminopyridine structural motif commonly shows potent bioactivities and therefore has been incorporated in chemotherapeutic agents such as antibacterials, α-MSH-stimulated melanogenesis inhibitors, and SSTR4 agonists . In addition, this class of molecular scaffold can be employed as the Comins–Meyers amide reagents in the syntheses of a variety of alcohols, ketones, and esters.…”
Section: Introductionmentioning
confidence: 99%